Cryopreservation of human embryonic stem cells and hepatocytes - Chen, S (2013)
Cell cryopreservation has been used for cell banking, but has proven to be challenging concerning some important cells such as human embryonic stem cells (hESCs) and human primary hepatocytes. Cells can lose their viability or functions following cryopreservation. It is the aim of this study to develop novel methods and to optimise the common protocols to improve the outcome of cryopreservation of hESCs and human primary hepatocytes. Experiments were carried out to establish the cell culture and functional assays of hESC and isolation, purification and functional assays of human primary hepatocytes. Three-dimensional encapsulation using RGDS-alginate and cryopreservation were applied to hESC as well as freshly isolated human hepatocytes and the results were compared to conventional cryopreservation of these cells in suspension. Important parameters, such as the concentration of cryoprotective agents (CPAs), freezing rate, loading time, thawing protocols, subsequent culture methods and their effect on cell viability and functions were all studied experimentally. Electroporation and Sonoporation were explored as possible methods to promote and mediate cell membrane transport of non-permeable CPAs, i.e. trehalose, to protect the intracellular components of the cells. It was concluded that the RGDS-alginate encapsulation improves the hESC cryopreservation outcome. The human primary hepatocytes, successfully isolated from liver tissue samples, can be cryopreserved with fairly high cell survival rate and functionality. Challenges and future research areas were identified, including optimization of 3D cryopreservation of human primary hepatocytes, effect of RGDS-alginate encapsulation on cell apoptosis of cryopreserved hESC and application of electroporation and sonoporation to the preservation of the hESCs and human hepatocytes.